2020
DOI: 10.1177/1056789520923720
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive model of rock triaxial damage based on the rock strength statistics

Abstract: Firstly, an X-ray diffraction test is carried out to investigate brittle rock specimens’ composition, and a triaxial compression test is conducted to study the deformation behaviors and mechanical properties. Then, assuming that the rock material is able to be divided into the elastic part satisfying the Hooke’s law and the damage part where rock strength follows lognormal distribution, this paper determines a damage variable and establishes a damage constitutive model which effectively reflects the residual s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 66 publications
0
37
0
Order By: Relevance
“…In this case, the dynamic properties of underground excavations, including strength, moduli, etc. may increase, while the energy for rock fracture decreases and even negative values (Chen, 2020;Li et al, 2017Li et al, , 2020Zhu et al, 2021). The dynamic failure process of surrounding rock is violent, which is often considered as rockburst.…”
Section: Dynamic Failure Pattern Identification Of Surrounding Rockmentioning
confidence: 99%
“…In this case, the dynamic properties of underground excavations, including strength, moduli, etc. may increase, while the energy for rock fracture decreases and even negative values (Chen, 2020;Li et al, 2017Li et al, , 2020Zhu et al, 2021). The dynamic failure process of surrounding rock is violent, which is often considered as rockburst.…”
Section: Dynamic Failure Pattern Identification Of Surrounding Rockmentioning
confidence: 99%
“…Many studies have shown that before the appearance of macro-cracks due to loads, the mechanical properties of materials are affected by local micro-cracks (Chan et al, 1997;Ji et al, 2011;Liu and Su, 2016). According to the hypothesis of strain equivalence, the damage constitutive model of materials can be expressed as follows (Chen, 2020;Lemaitre, 1984;Xie et al, 2020) r ¼Ẽe ¼ Eeð1 À DÞ…”
Section: Model Buildingmentioning
confidence: 99%
“…Based on the exponential function of bolt load displacement curve proposed in reference (Ying et al, 2005), a modified exponential function model is proposed by introducing statistical damage mechanics (Rinaldi et al, 2007;Chen, 2020;Xie et al, 2020). By analyzing the deterioration law of the pullout stiffness of the exponential function model, it is found that the pullout stiffness of the bolt in the model decreases exponentially with the displacement.…”
Section: Introductionmentioning
confidence: 99%